Image-Guided Ablation of Renal Masses: Challenges to Produce High-Quality Evidence and Future Directions - Chan, Vinson Wai-Shun; Ng, Helen Hoi-Lam; Wah, Tze Min (Seminars in Interventional Radiology, 2024)
Image-guided ablation (IGA) is a rapidly developing field in interventional oncology. There is some evidence suggesting IGA's non-inferiority compared with partial or radical nephrectomy for the treatment of small renal masses (SRM). However, these are mostly limited to retrospective cohort studies. This review article outlines the evidence comparing IGA to partial nephrectomy by collating the different survival measures and evaluates the challenges of producing clinical trials and high-quality evidence. The main challenges are due to the heterogeneity of SRM, patient selection bias, unstandardized endpoint and outcomes, and the lack of global practice standards. Despite the evidence thus far demonstrating that IGA stands as a non-inferior treatment modality for SRMs, exhibiting favorable short- and long-term outcomes, further robust research is needed to integrate ablation techniques into routine clinical practice with a multidisciplinary approach. There is emerging evidence that suggests randomized controlled trial in SRMs is possible, and technologies such as histotripsy as well as artificial intelligence are used in IGA.
Keywords: ablation; clinical trial; renal mass; renal cancer; interventional radiology